The Effectiveness of Diabetes Self-Management Education (DSME) on the Self-Care of Patients with Diabetic Foot Ulcers - Candra Kusuma Negara; Hery Wibowo; Rizka Hayyu Nafi'ah; Ricky Prawira (Indonesian Journal of Global Health Research, 2025)
Diabetic foot ulcers are one of the chronic complications of diabetes mellitus (DM) that can lead to serious infections and even amputation. Poor self-care ability is a major risk factor in the development of chronic wounds among DM patients. The Diabetes Self-Management Education (DSME) intervention has been considered effective in improving patients’ self-management abilities; however, contextual evidence in Indonesia remains limited. This study aimed to evaluate the effectiveness of DSME intervention in improving self-care abilities among patients with diabetic foot ulcers at RSUD Banjarmasin. The study employed a quasi-experimental design using a one group pre-test and post-test approach. A total of 30 patients were selected using total sampling. The DSME intervention was delivered over seven consecutive days through a structured, face-to-face educational approach. Self-care ability was measured using the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire before and after the intervention. Data were analyzed using a paired sample t-test. Prior to the intervention, the majority of respondents (70%) were categorized as having poor self-care. After the intervention, 80% of respondents were categorized as having good self-care. The paired sample t-test showed a significant difference in self-care scores before and after the DSME intervention (p < 0.001). The DSME intervention was effective in enhancing self-care abilities among patients with diabetic foot ulcers.